The gut-lung axis: effects and mechanisms of gut microbiota on pulmonary diseases - Liu, Jiaxin; Hong, Weichen; Sun, Zhendong; Zhang, Shuyu; Xue, Chenyu; Dong, Na (Frontiers in Immunology, 2026)
The proposal of the gut–lung axis has profoundly reshaped our understanding of the mechanisms underlying respiratory diseases. As a crucial component of this axis, the gut microbiota plays a central role in pulmonary immune regulation through inter-organ communication mediated by metabolic products. However, a systematic integration of mechanisms explaining how gut microbes achieve precise cross-organ immune regulation remains elusive. Existing research predominantly focuses on descriptive observations, such as the association between early-life microbiota dysbiosis and an increased risk of asthma and chronic obstructive pulmonary disease (COPD), as well as the frequent occurrence of acute respiratory distress syndrome (ARDS) and pulmonary fibrosis (PF), often accompanied by gut microbiome disruption. This paper focuses on three key gut microbial metabolites—short-chain fatty acids (SCFAs), tryptophan metabolites, and polyamines (PAs)—to examine their roles in immune regulation, maintenance of barrier function, and modulation of metabolic signaling networks. Based on the latest experimental and clinical evidence, this study systematically elucidates how dysbiosis of the gut microbiota, a key component of the gut-lung axis, crosses physiological barriers to exacerbate pulmonary inflammation. Regarding intervention strategies, probiotics, fecal microbiota transplantation (FMT), and CRISPR-Cas systems have demonstrated significant therapeutic potential in restoring gut microbial balance. Finally, this paper outlines future research directions, emphasizing the need to further explore non-invasive microbial sampling techniques, molecular interaction mechanisms of the gut-lung axis, and personalized microbiome-based diagnostic and therapeutic strategies to provide new insights for the prevention and treatment of respiratory diseases involving gut microbiota.